2011
DOI: 10.1159/000322625
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Restraint Stress Reduces the Number of IgA-Producing Cells in Peyer’s Patches

Abstract: The few reports that have analyzed the effects of stress on the immune cells of the intestinal mucosa or the functions of these cells have tended to focus on S-IgA levels in saliva, and these studies have shown contradictory results. The principal objective of this study was to analyze the effects of repeated restraint stress on the number and distribution of immune cells in Peyer’s patches (PPs) as well as the effects of glucocorticoid and catecholamine administration on the same stress-related parameters. Up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…These suppressive effects of restraint stress were mimicked by the administration of pharmacological dose of catecholamines and glucocorticoids, results suggested the activation of two pathways–- the sympathetic autonomic nervous system and the HPA axis (Jarillo-Luna et al, 2007, 2008; Martínez-Carrillo et al, 2011). In another study, the endogenous production of glucocorticoids, triggered by a continuous 12-h period of restraint stress, decreased the number of T and B cells in Peyer’s patches, which is in line with a reduction in the levels of intestinal SIgA and lymphocytes (Sudo et al, 2001).…”
Section: The Restraint Model and The Influence Of Stress In The Intesmentioning
confidence: 92%
See 1 more Smart Citation
“…These suppressive effects of restraint stress were mimicked by the administration of pharmacological dose of catecholamines and glucocorticoids, results suggested the activation of two pathways–- the sympathetic autonomic nervous system and the HPA axis (Jarillo-Luna et al, 2007, 2008; Martínez-Carrillo et al, 2011). In another study, the endogenous production of glucocorticoids, triggered by a continuous 12-h period of restraint stress, decreased the number of T and B cells in Peyer’s patches, which is in line with a reduction in the levels of intestinal SIgA and lymphocytes (Sudo et al, 2001).…”
Section: The Restraint Model and The Influence Of Stress In The Intesmentioning
confidence: 92%
“…Experimental assays have evidenced that the stress modulates the generation of secretory immunoglobulin A (SIgA; Jarillo-Luna et al, 2007; Martínez-Carrillo et al, 2011) and the expression of pIgR (Reyna-Garfias et al, 2010). Through transcytosis this receptor transports immunoglobin-pIgR complexes (dIgA-pIgR and pIgA-pIgR) across gut epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the Canadian Healthy Infant Longitudinal Development cohort, infants born to mothers with prenatal depressive symptoms only and those with both pre‐ and early postnatal depressive symptoms had reduced secretory IgA in stools . This was possibly due to a lowering of plasma cells in Peyer's patches as a consequence of glucocorticoid and catecholamine release after exposure to stress . Infants’ secretory IgA is a first‐line defense of the immature immune system against infections with the capacity to influence the composition of gut microbiota, a potential pathway linking maternal prenatal stress and infant health .…”
Section: Discussionmentioning
confidence: 99%
“…26 This was possibly due to a lowering of plasma cells in Peyer's patches as a consequence of glucocorticoid and catecholamine release after exposure to stress. 27 Infants' secretory IgA is a first-line defense of the immature immune system against infections with the capacity to influence the composition of gut microbiota, a potential pathway linking maternal prenatal stress and infant health. 28,29 The relationship between postnatal stress and infections in offspring might be due to an increased susceptibility of F I G U R E 2 Univariable and multivariable log-binomial regression models for categories of GHQ-12 score (high prenatal-low postnatal; low prenatalhigh postnatal; high pre-and postnatal) and outcomes in offspring.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to increase or decrease intestinal IgA levels, effects which may be species-dependent (Alverdy and Aoys 1991;Spitz, Ghandi et al 1996;Reyna-Garfias, Miliar et al 2010;Lyte, Vulchanova et al 2011). Other studies have demonstrated that GCsreduce the number of IgA-producing cells in Peyer's patches of mice (Martinez-Carrillo, Godinez-Victoria et al 2011), decrease the number of intraepithelial lymphocytes (IEL) in the proximal small intestine of mice (Jarillo-Luna, Rivera-Aguilar et al 2007;Jarillo-Luna, Rivera-Aguilar et al 2008;Reyna-Garfias, Miliar et al 2010),andincrease the levels of mRNA for pIgR in the proximal duodenum of suckling rats (Li, Wang et al 1999). Thus,it may be through the liberation of GCs that the CNS regulates the production and secretion of intestinal IgA specific to Salmonella.…”
Section: Glucocorticoids and Igamentioning
confidence: 99%